(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper an analysis presented to investigate the influence of radiation absorption, chemical reaction and heat source effects on hydro magnetic free convection heat and mass transfer flow of visco-elastic fluid through porous medium bounded by an oscillating porous plate in the slip flow regime with constant suction and temperature dependent heat source. A uniform magnetic field of strength B0 is applied at an angle α with the field flow direction. Analytical solutions for velocity, temperature and concentration are obtained. Skin friction, rate of heat and mass transfer coefficients are also derived. The results have been analyzed and presented graphically for various values of the flow parameters. It is observed that velocity increases with an increase in porosity parameter, radiation absorption, Grashof number, modified Grashof number and it decreases with an increase in magnetic parameter, Schmidt number, chemical reaction parameter, Prandtl number.